Determination of energy requirement for maintenance of adult non-lactating crossbred cows - GHOSH, A; MURARILAL, MURARILAL; HAQUE, N; KHAN, M Y (The Indian Journal of Animal Sciences, 2014)
Adult, non-lactating, non-pregnant, crossbred cows (6; 1/2 Holstein-Friesian x 1/2 Hariana), 7-to 8-year-old, weighing 334 to 438 kg, were divided into 2 groups of3 animals in each and fed at 2 different levels of feeding. The animals in both the groups were fed on isonitrogenous diets having 100 and 80% of metabolizable energy (ME) requirement in groups 1 (OE) and 2 (LE) respectively. Energy balance was determined in both the groups in open circuit respiration chamber in phase 1. In phase 2. animals in both the groups were interchanged and balance studies were repeated. Fasting heat production was determined individually in all the animals at the end of the experiment. The dry-matter intake was 73. 7Â±0.86 and 63.7Â±0.65 g/kg W0.75/day in OE and that in LE groups, respectively. The dry matter intake in OE group was significantly (P